Contemporary methods of prevention and early detection of cervical cancer - a review of the literature - Ewelina Zygmunt; Dariusz Chojeta; Aleksandra Zimna; Hubert Wróblewski; Barbara Maziarz; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Cervical carcinoma remains a significant health problem, despite the progressive fall in the mortality rate during the past 60 years. However, cervical carcinoma is still the most common cancer among women worldwide and the leading cancer cause of death in many countries.  The primary strategy to reduce the incidence and death rate from cervical carcinoma is screening by cervical cytology. The knowledge that persistent human papillomavirus (HPV) infection is the main cause of cervical cancer has resulted in the development of prophylactic vaccines to prevent HPV infection and HPV assays that detect nucleic acids of the virus. This study is a review of currently available methods of prevention and early detection of cervical cancer.